2021
DOI: 10.3389/fpls.2021.784037
|View full text |Cite
|
Sign up to set email alerts
|

Natural Variation in OsMKK3 Contributes to Grain Size and Chalkiness in Rice

Abstract: Rice (Oryza sativa L.) is an important staple food crop for more than half of the world’s population. Enhancing the grain quality and yield of rice to meet growing demand remains a major challenge. Here, we show that OsMKK3 encode a MAP kinase kinase that controls grain size and chalkiness by affecting cell proliferation in spikelet hulls. We showed that OsSPL16, GS5, and GIF1 have a substantial effect on the OsMKK3-regulated grain size pathway. OsMKK3 has experienced strong directional selection in indica and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 57 publications
2
12
0
Order By: Relevance
“…Furthermore, we found yield-related genes and rice quality-related metabolites ( Table 3 ; Figure 5 ; Figure S6 ). The grain length of hybrid indica rice is closely related to rice quality, and the slender grains allow for fuller grain filling and better appearance and eating quality [ 27 ]. This study found the same phenomenon in TF varieties with slender grains ( Figure 6 H), and the rice quality was rated as national standard high-quality rice grade one.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found yield-related genes and rice quality-related metabolites ( Table 3 ; Figure 5 ; Figure S6 ). The grain length of hybrid indica rice is closely related to rice quality, and the slender grains allow for fuller grain filling and better appearance and eating quality [ 27 ]. This study found the same phenomenon in TF varieties with slender grains ( Figure 6 H), and the rice quality was rated as national standard high-quality rice grade one.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the extensive germplasm resources of Guangxi, a typical common wild rice accession DP15 with several important economic traits was identified and selected to develop a set of CSSLs ( Figure S1 ). Our investigation revealed the significant phenotypic difference in various morphological traits observed between DP15 and the indica rice variety 93-11, including PH, awn length, leaf width, LMC, tiller number, tiller angle, spreading panicle, seed color, seed shattering, seed dormancy, GN, GL, GW, TGW, GLWR, and so on [ 72 ]. Through the WGRS, the genomic differences were highlighted by the bioinformatic analysis in this study, and 12,565 pairs of polymorphic InDel markers were designed to establish DP15-CSSLs and mining for novel genome QTLs.…”
Section: Discussionmentioning
confidence: 99%
“…OsMKK3 [17], and OsGASR7 [18]. However, many unknown genes and proteins have yet to be discovered, and the identification of these genes and proteins is essential for achieving a complete understanding of the molecular network underlying the regulation of grain size.…”
Section: Introductionmentioning
confidence: 99%